Comparison of Ketorolac Versus Diclofenac as Treatment for Acute Renal Colic: A Systematic Review and A Network Meta-Analysis - Eko Arianto; Arry Rodjani; Irfan Wahyudi (PT. Kalbe Farma Tbk., 2017)
Acute renal colic is one of the most frequent urologic visits in Emergency Department (ED), and early management should focus on early relief of pain. Non-steroidal anti-inflammatory drugs (NSAIDs), opiates, or combination of both are often used to treat this condition. Diclofenac is stated in European Association of Urology (EAU) guideline as first line treatment. Interestingly, it is ketorolac that currently the most common analgesics used in most EDs. A meta-analysis study was designed to investigate whether ketorolac or diclofenac is a better NSAID for early pain relief in acute renal colic patients. Relevant studies were obtained from PubMed, Science Direct, Cochrane, EBSCO, and Proquest. Based on current studies, both ketorolac and diclofenac are found superior than pethidine, while both providing a comparable pain relief with diclofenac regarded as a safer option. Further prospective data is needed in Indonesian clinical settings for its assurance in efficacy and safetyKolik ginjal akut adalah salah satu kunjungan urologi yang paling sering di departemen darurat (Emergency Department/ED), dan manajemen dini fokus untuk mengatasi rasa nyeri. Obat antiinflamasi nonsteroid (NSAID), opiat, atau kombinasi keduanya sering digunakan untuk mengatasi kondisi ini. Diklofenak disebutkan dalam pedoman European Association of Urology (EAU) sebagai pengobatan lini pertama. Menariknya, ketorolak adalah analgesik paling umum yang digunakan pada kebanyakan ED. Sebuah studi meta-analisis dirancang untuk mengetahui apakah ketorolak atau diklofenak adalah NSAID yang lebih baik untuk menghilangkan nyeri pada pasien kolik ginjal akut. Studi yang relevan diperoleh dari PubMed, Science Direct, Cochrane, EBSCO, dan Proquest. Berdasarkan penelitian-penelitian tersebut, ketorolak dan diklofenak ditemukan lebih unggul daripada pethidin, sementara keduanya menghilangkan rasa sakit yang sebanding, dengan diklofenak yang dianggap sebagai pilihan yang lebih aman. Data prospektif lebih lanjut diperlukan untuk penggunaan klinis di Indonesia untuk memastikan efektivitas dan keamanannya.